1968 in the Literary Production of Colombia: Individual, Violence and Society (2017)
This article analyzes the reception of several literary works in Colombia during the year 1968, aimed at offering a vision of the relation between society, the individual and violence as social representation and indicator of cultural impact. Through the identification of these three topics: the individual, violence and society, this study examines literary consumption in Colombia as an indicator of a desire of change, articulated with the planetary cultural revolution of 1968. Through the identification of the most read works of literature in Colombia during this year, and based on the impact of these works on public opinion and culture, this study analyzes the relation between individual-society-violence, with the objective of visibilizing certain organizational processes during the 1960s and 70s, not only in Colombia but in Latin America. This article is divided into three independent but interconnected sections, each one of which analyzes some of the most important objects of literary consumption of the time and ends with a study of the incidence of these texts on the Colombian population.